Pengaruh Digital Marketing dan Harga Terhadap Minat Beli Konsumen Pasca Covid di UMKM Kerajinan Kayu Nyiur Indah Singaraja - Kadek Ari Ardiari; Ni Nyoman Juli Nuryani (UNHI Press, 2023)
This study aimed to find out the effect of digital marketing on post-covid consumers' buying interest in the Nyiur Indah Singaraja Wood Crafts MSMEs and to find out the effect of price on post-covid consumers' buying interest in the Nyiur Indah Singaraja Wood Crafts MSMEs. The type of research used is quantitative. The results showed: 1) Digital marketing has a positive and significant effect on consumer buying interest in MSMEs Nyiur Indah Singaraja Wood Crafts. This is shown from the results of hypothesis testing which obtains a positive regression coefficient value of 0.160; t count value of 2.166 > 1.66; and a significance value of 0.033 <0.05. 2) Price has a positive and significant effect on consumer buying interest in MSMEs Nyiur Indah Singaraja Wood Crafts. This is shown from the results of hypothesis testing which obtained a positive regression coefficient value of 0.433; t count value of 5.184 > 1.66; and a significance value of 0.000 <0.05.